Radiated emissions from power feeders for electric propulsion in aircraft - Lansink Rotgerink, J.H.G.J. (IEEE, 2022)
Electric propulsion is a major focal point for aviation industry towards achievement of international sustainability goals. These developments will cause an inevitable increase in on-board power levels, implying higher voltages and currents. One of the various corresponding challenges in electromagnetic compatibility concerns the radiated emissions of power feeders. This paper focusses on the modelling of these emissions from three-phase power feeders by a combination of multiconductor transmission line modelling for determination of the currents in power feeders, and the Hertzian Dipole method to determine the radiated electric fields. Simulations and measurements are performed on the case of a single wire above ground, as well as a three-phase power feeder, resulting in a good match between theory and practice. The obtained simulation methods can also be used in combination with actual currents flowing onto the cabling, obtained either from measurements or simulations, to estimate the total in situ radiated emissions from three-phase power feeders.